A comparative study of Runway Temperature and Screen Temperature observations made at Dum Dum Airport: Reports of a preliminary study (MAUSAM, 1963)
Result of a prelin1inary study of runway and screen ten1perature readings recorded at Dum Dum Airport at six synoptic hours (at 0000, 0300, 0600, 0900, 1200 and 1800 GMT) for a period of 21 months (from February 1959 to October 1960) is reported in this short communication, It has been found that the difference of ten1peraturereadings is generally less than 1°C except during winter and pre. It level monsoon seasons for a period from a couple of hours after sunrise to about 0600 GMT, It has also been found that the runway temperature is generally higher than the screen ten1perature, The reason for the higher values of runway temperature has been attributed to radiation effect.